Proposing Islamic Values Implementation in Workplace:Analysis via Rasch Model - Hayati Ishak, Amal; Khadijah Ab Manan, Siti; Saidon, Rafeah; Huda Sahari, Noorul (International Journal of Engineering and Technology, 2018)
Previous and current research has long been indulged into empirical study of values. Nevertheless, these research are limitedly focused on the influence of values to performance or other variables, and undoubtedly agree on the significant function of values in workplace. However, guiding principles for organisations to apply the values in working environment has been marginally suggested or provided, as a by-product of scientific research. Thus this article proposes two sets of values application in workplace; the basic and advanced practices of values. The first refers to introductory values which should be introduced to organisational members prior to the letter. The sets of values are resulted from Rasch Model analysis of item difficulty and person ability.